Longstanding Use of Tapentadol Hydrochloride Nasal Spray Resulting in Palatal Perforation − A Case Report - Santosh K. Swain; Pradipta K. Parida; Safia Saleem (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Palatal perforation or oronasal fistula is an uncommon clinical entity. It may result from acquired or congenital factors. The three common acquired causes of palatal perforations are drug addiction, cancer, and infections. Appropriate history-taking and risk factor assessment assist in diagnosis. The two common symptoms associated with oronasal fistula include nasal regurgitation and speech problems. For histological study, palatal lesions should be biopsied. It is necessary to get the proper cultures and stains for fungus, bacteria, and mycobacteria. Depending on the underlying etiology, palatal perforations have different treatment options and prognoses. In this instance, we report a palatal perforation brought on by a long-term tapentadol hydrochloride nasal spray user.